2016
DOI: 10.1097/md.0000000000002484
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Hypersomnia Concurrent With Recovery of an Injured Ascending Reticular Activating System in a Stroke Patient

Abstract: We report on a stroke patient who showed recovery of hypersomnia concurrent with the recovery of an injured ascending reticular activating system (ARAS), which was demonstrated by diffusion tensor tractography (DTT).A 70-year-old female patient underwent coiling of the left ruptured posterior communicating artery after subarachnoid hemorrhage and both extraventricular drainage for management of an intraventricular hemorrhage. At 2 months after onset, when she started rehabilitation, she exhibited intact consci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Subsequently, a study demonstrated recovery from hypersomnia with recovery of injured dorsal and ventral (more recovery than the dorsal lower ARAS) lower ARAS in a patient with subarachnoid hemorrhage. [ 4 ] Recently, Jang et al reported on patients with hypersomnia and injury of the dorsal and ventral (more injury than the lower dorsal ARAS) lower ARAS in patients with pontine hemorrhage (1 patient) and mild TBI (2 patients), respectively. [ 5 , 6 ] These studies suggest that injury of the ARAS could be a probable cause for the hypersomnia in patients with brain injury particularly TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a study demonstrated recovery from hypersomnia with recovery of injured dorsal and ventral (more recovery than the dorsal lower ARAS) lower ARAS in a patient with subarachnoid hemorrhage. [ 4 ] Recently, Jang et al reported on patients with hypersomnia and injury of the dorsal and ventral (more injury than the lower dorsal ARAS) lower ARAS in patients with pontine hemorrhage (1 patient) and mild TBI (2 patients), respectively. [ 5 , 6 ] These studies suggest that injury of the ARAS could be a probable cause for the hypersomnia in patients with brain injury particularly TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report an association between injury of the hypothalamus with sleep disorders, such as narcolepsy and hypersomnia, following TBI (Baumann et al, 2005 , 2009 ; Valko et al, 2015 ; Jang and Kwon, 2016 ; Jang et al, 2016b , c ; Jang and Lee, 2017 ). In addition, since the reconstruction of the ARAS using DTT is possible, many studies have demonstrated that the lower ventral ARAS, which is connected to the hypothalamus, is closely related with hypersomnia following brain injury (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ). Therefore, the results of our study appear to be consistent with previous studies (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the reconstruction of the ARAS using DTT is possible, many studies have demonstrated that the lower ventral ARAS, which is connected to the hypothalamus, is closely related with hypersomnia following brain injury (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ). Therefore, the results of our study appear to be consistent with previous studies (Jang and Kwon, 2016 , 2017 ; Jang et al, 2016a , b , 2017 , in press ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Jang et al [11] demonstrated injury of the lower ventral ARAS in a patient who showed hypersomnia and narcolepsy following mild traumatic brain injury. During the same year, Jang et al [12] reported on a patient who showed recovery of hypersomnia concurrent with the recovery of an injured lower dorsal and ventral ARAS following spontaneous subarachnoid hemorrhage. This patient also showed more severe injury and more recovery of the lower ventral ARAS than the lower dorsal ARAS.…”
Section: Discussionmentioning
confidence: 99%